2017
DOI: 10.3390/molecules22122055
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Inactivation of Triosephosphate Isomerase from Trypanosoma brucei: Kinetic and Molecular Dynamics Studies

Abstract: Human African Trypanosomiasis (HAT), a disease that provokes 2184 new cases a year in Sub-Saharan Africa, is caused by Trypanosoma brucei. Current treatments are limited, highly toxic, and parasite strains resistant to them are emerging. Therefore, there is an urgency to find new drugs against HAT. In this context, T. brucei depends on glycolysis as the unique source for ATP supply; therefore, the enzyme triosephosphate isomerase (TIM) is an attractive target for drug design. In the present work, three new ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…However, it did not explore in detail the interactions between the two monomers. The simulations that report the root-mean-square fluctuation (RMSF) of TIM proteins have consistently found the highest RMSF values in loops 5 and 6 22,24,25 , which is in good agreement with our work.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, it did not explore in detail the interactions between the two monomers. The simulations that report the root-mean-square fluctuation (RMSF) of TIM proteins have consistently found the highest RMSF values in loops 5 and 6 22,24,25 , which is in good agreement with our work.…”
Section: Introductionsupporting
confidence: 90%
“…Circular dichroism indicated that the chimeric proteins had the same fold as the native, however, the role that these mutations have on the structure and dynamics of the proteins is not well understood. For many years, studies have focused on the interaction between TIM proteins and benzothiazoles, which have been found to deactivate the enzyme 13,22,23 . While there is a plethora of experimental data, there are very few MD simulations of TcTIM and TbTIM in the absence of ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8–12 ] Also, some works have proposed a selective target, such as the enzyme triosephosphate isomerase (TIM) [ 13 ] ; this glycolytic enzyme has been used as a therapeutic target for the development of new drugs against various pathogenic organisms, such as Trypanosoma cruzi , Trypanosoma brucei , E. histolytica , Giardia duodenalis , Trichomonas vaginalis , Clostridium perfringens , among others. [ 14–24 ] In addition, other researchers are looking for the repositioning of commercial drugs as antiparasitics. [ 25,26 ] The triosephosphate isomerase of E. histolytica (EhTIM) [ 27 ] has an identity of 41.33% with human TIM (HsTIM); this difference in amino acids favors the development of new drugs with a selective target against EhTIM.…”
Section: Introductionmentioning
confidence: 99%
“…In the pharmaceutical industry, the development of selective drugs to an enzyme or the repositioning of commercial drugs, today, is booming. The glycolytic enzyme triosephosphate isomerase (TIM) has been used as a therapeutic target for the development of new drugs against various pathogenic organisms, such as, Trypanosoma cruzi, Trypanosoma brucei, Entamoeba histolytica, Giardia duodenalis, Trichomonas vaginalis , among others . Therefore, saving resources in the development of new drugs, by directing the interaction of pharmacological compounds to a specific interaction site with a high probability to be selective, represents an opportunity, for researchers who are looking for new molecules or pharmacological compounds that they do not have a reported use, or in the case, of wanting to find another use to conventional drugs, such as omeprazole against TIM [11] [12] .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we propose a potential site as a therapeutic target against the enzyme triosephosphate isomerase for drug development, and that this potential new drug could be safe to be used at humans. We determined the K in position 214 (near the sequence YGGSV−K214) is indispensable for the interaction with the tested compounds and it helps the interaction in the active site from TIM.…”
Section: Introductionmentioning
confidence: 99%